Perceived Value of the Electronic Health Record and Its Association with Physician Burnout - Livaudais, Maria; Deng, Derek; Frederick, Tracy; Grey-Theriot, Francine; Kroth, Philip J. (Applied Clinical Informatics, 2022)
Background There is a common belief that seniority and gender are associated with clinicians' perceptions of the value of electronic health record (EHR) technology and the propensity for burnout. Insufficient evidence exists on the relationship between these variables.Objective The aim of this study was to investigate how seniority/years of practice, gender, and screened burnout status are associated with opinions of EHR use on quality, cost, and efficiency of care.Methods We surveyed ambulatory primary care and subspecialty clinicians at three different institutions to screen for burnout status and to measure their opinions (positive, none, negative, don't know) on how EHR technology has impacted three important attributes of health care: quality, cost, and efficiency of care. We used chi-square tests to analyze association between years of practice (≤10 years or 11+ years), gender, and screened burnout status and the reported attributes. We used a Bonferroni-corrected α = 0.0167 for significance to protect against type I error among multiple comparisons.Results Overall, 281 clinicians responded from 640 that were surveyed with 44% overall response rate. There were no significant associations of years in practice (≤10 years or 11+ years) or gender (p > 0.0167 for both) with any of the health care attributes. Clinicians who screened burnout negative (n = 154, 55%) were more likely to indicate that EHR technology has a positive impact on both the quality (p = 0.0025) and efficiency (p = 0.0003) health care attributes compared with those who screened burnout positive (n = 127, 45%).Conclusion Burnout status is significantly associated with clinicians' perceived value of EHR technologies, while years of practice and gender are not. This contests the popular notion that junior clinicians view EHR technology more favorably than their more senior counterparts. Hence, burnout status may be an important factor associated with the overall value clinicians ascribe to EHR technologies.
Keywords: people; burnout; documentation burden; workflows and human interactions; human–computer interaction; interfaces and usability; culture; workarounds and unanticipated consequences; user acceptance and resistance